Collaboration between the World Bank and ECFS in developing case study approach for food policy in Eurasia: Experience and lessons learned - Hakobyan, Artavazd (2020)
Artavazd Hakobyan POLICY SEMINAR Virtual Event - Food Policy Research and Capacity Development in Eurasia Co-Organized by the Eurasian Center for Food Security (ECFS), World Bank Group, and IFPRI DEC 2, 2020 - 07:30 AM TO 09:00 AM EST